2009
DOI: 10.1007/978-3-642-03432-9_17
|View full text |Cite
|
Sign up to set email alerts
|

Jahn–Teller Effects in Molecules on Surfaces with Specific Application to C60

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Abstract Scanning tunnelling microscopy (STM) is capable of imaging molecules adsorbed onto surfaces with sufficient resolution as to permit intramolecular features to be discerned. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…However, some preliminary results, concerned with the dynamical aspect of the problem as applied to E e and T h coupling regimes, including a discussion relating to charge transfer, may be found in Ref. 36.…”
Section: Discussionmentioning
confidence: 99%
“…However, some preliminary results, concerned with the dynamical aspect of the problem as applied to E e and T h coupling regimes, including a discussion relating to charge transfer, may be found in Ref. 36.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the interaction of a C 60 anion with a surface will also lead to a distortion of a system. It has therefore been suggested that surface interactions could be written (again phenomenologically), at least to a first approximation, in terms of an expansion in the σ λ for an h mode, which would result in a similar symmetry-lowering distortion to that used to describe co-operative JT effects [30]. However, to do this, the relevant operators must have a symmetry appropriate to that of both the adsorbed molecule and of the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Our treatment has ignored the effect of these displacements on STM images, as these are expected to be negligibly small. Significant displacement of the nuclei during pseudorotation would 'blur' the images presented here, as in the case of an E ⊗ e system [2].…”
Section: Summary and Discussionmentioning
confidence: 96%
“…The results are also shown in table 1. As the timescale of an STM experiment is expected to be orders of magnitude larger than the time taken to tunnel between equivalent configurations [2], all equivalent (isoenergetic) distortions in a set will be imaged together in an STM experiment. In the table, groups on the same line separated by braces are related to each other by reflections in the x-z plane.…”
Section: Surface Interactions In General Termsmentioning
confidence: 99%
See 1 more Smart Citation